(untitled) (Research, Society and Development, 2022)
This study aims to reflect on experiences and learning in a field trip that took place in the Amondawa indigenous village, in Mirante da Serra, 2019, a collective work, developed by the team of teachers from Agricultural Family School Vale do Guaporé and Students, with an indigenous community. The study trip is part of the school’s training plan and was built through the pedagogy of alternation, the main objective being to have an experience in the indigenous village; it was the history of the narrative peoples of life, well knowing their space, having as main theoretical basis the dialogue with Paulo Freire. The methodology used was qualitative, with bibliographic research, in order to contextualize the field trip in the village. Our results show as enriching experiences for teachers, in which it was possible to enrich a team of teachers and students, a joint experience of faith experiences such as dialogues, exchanges. Throughout their practices, their practices, their villages, their lives, their plays, their practices, their lives, their lives, their plays, their constructed parts, their constructed objects and their narratives of life. After this class, with travel materials made in Brazil, the debate took place in relation to the history of peoples and current issues. A very important journey of faith for the school and the indigenous community, and in this process theory and practice provide an opportunity for significant and critical learning.